Upaya Pemanfaatan Limbah Bonggol Jagung menjadi Briket sebagai Bahan Bakar Alternatif di Desa Jadi Semanding Tuban - Muhibbulloh, Muhammad Za'im; Putra, Dito Amanda; Anikmah, Anikmah; Fidiyanti, Fiya; Fitrotin, Evita Zayyinatul; Utomo, Achmad Wahyu Priyo; Nisa', Istiqomatin; Rosidah, Amirur; Andika, Sukron Ma'mun; Nashihah, Siti Roudlotun; Wijaya, Abdul Latif Akbar; Wahyudhi, Ilham Tri (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
This community service activity was carried out in Jadi Village, Semanding District, Tuban Regency, aiming to utilize corn cob waste into briquettes as an environmentally friendly and economically valuable alternative fuel. The method applied was the Asset-Based Community Development (ABCD) approach through the stages of Discovery, Dream, Design, Define, and Destiny, involving observation, interviews, socialization, and participatory training. The results showed that corn cob waste, which had previously been discarded, can be processed into briquettes using simple technology, low costs, and abundant raw materials. The production process includes burning the corn cobs into charcoal, grinding, mixing with natural binders, molding, and drying. This program has enhanced community skills, reduced agricultural waste, and created new business opportunities. Challenges encountered include the dependence on sunlight for drying and limited marketing reach. Future development can be achieved through the establishment of joint business groups, packaging innovation, and expansion of distribution networks.